Level of Management Performance of the Provincial Municipality of Chota: A Methodology for Local Governments - Quiroz Mejía, José Ricardo (2022)
This descriptive, quantitative, non-experimental (non-probabilistic, targeted sample) and cross-sectional research aimed to determine the level of management performance of the Provincial Municipality of Chota (MPCH). The results showed that the MPCH has a low level of efficiency, effectiveness, collaboration, transparency and ethics; therefore, it was concluded that an analysis of the municipal administration from the “New Public Governance” and “Institutional Strategic Planning” dimensions provided a methodology to diagnose the management of the MPCH, which may be useful for other local governments.